2021
DOI: 10.1088/1361-6560/abf2f7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy-guided PET reconstruction using l 1 bowsher prior

Abstract: Advances in simultaneous positron emission tomography/magnetic resonance imaging (PET/MRI) technology have led to an active investigation of the anatomy-guided regularized PET image reconstruction algorithm based on MR images. Among the various priors proposed for anatomy-guided regularized PET image reconstruction, Bowsher’s method based on second-order smoothing priors sometimes suffers from over-smoothing of detailed structures. Therefore, in this study, we propose a Bowsher prior based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…This sometimes may result in over-smoothing of lesions with detailed structure, and this can be observed from the SD in tumors of the 32 patients (figure 6(b)), where the SD median from BCNN and BCNN0 are lower than the SD median of the MRAC, indicating over-smoothing. Most recently, the over-smoothing was addressed using an iterative weighting scheme and a first-order smoothing l 1 -norm by Kang and Lee (2021), and they reported that the mean uptake level of VOI was preserved while better detectability of small lesions was achieved. It is also worth mentioning that some tumor VOIs could have homogeneous texture where a lower SD is expected, while the SD will be higher in VOIs of heterogenies tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This sometimes may result in over-smoothing of lesions with detailed structure, and this can be observed from the SD in tumors of the 32 patients (figure 6(b)), where the SD median from BCNN and BCNN0 are lower than the SD median of the MRAC, indicating over-smoothing. Most recently, the over-smoothing was addressed using an iterative weighting scheme and a first-order smoothing l 1 -norm by Kang and Lee (2021), and they reported that the mean uptake level of VOI was preserved while better detectability of small lesions was achieved. It is also worth mentioning that some tumor VOIs could have homogeneous texture where a lower SD is expected, while the SD will be higher in VOIs of heterogenies tumors.…”
Section: Discussionmentioning
confidence: 99%
“…• Novel regularized PET image reconstruction techniques based on anatomical priors derived from concurrent MRI significantly improve PET image quality (173)(174)(175).…”
Section: Discussionmentioning
confidence: 99%
“…In PET, a number of different priors have been developed (Ehrhardt et al 2019, Kang andLee 2021). These priors have been mainly applied to the pixel model, however, a Gibbs prior (Brankov et al 2004) has been applied to a triangular mesh.…”
Section: Theorymentioning
confidence: 99%